Different modulation of short‐ and long‐latency interhemispheric inhibition from active to resting primary motor cortex during a fine‐motor manipulation task - Morishita, Takuya (Physiol Rep, 2014)
Performing a complex unimanual motor task markedly increases activation not only in the hemisphere contralateral to the task‐performing hand but also in the ipsilateral hemisphere. Transcranial magnetic stimulation studies showed increased motor evoked potential amplitude recorded in resting hand muscles contralateral to the task‐performing hand during a unimanual motor task, and transcallosal inputs from the active hemisphere have been suggested to have responsibilities for this phenomenon. In the present study, we used a well‐established double‐pulse transcranial magnetic stimulation paradigm to measure two phases of interhemispheric inhibition from the active to the resting primary motor cortex during the performance of a complex unimanual motor task. Two different unimanual motor tasks were carried out: a fine‐motor manipulation task (using chopsticks to pick up, transport, and release glass balls) as a complex task and a pseudo fine‐motor manipulation task as a control task (mimicking the fine‐motor manipulation task without using chopsticks and picking glass balls). We found increased short‐latency interhemispheric inhibition and decreased long‐latency interhemispheric inhibition from the active to the resting primary motor cortex during the fine‐motor manipulation task. To the best of our knowledge, the present study is the first to demonstrate different modulation of two phases of interhemispheric inhibition from the active to the resting primary motor cortex during the performance of a complex unimanual motor task. The different modulation of short‐ and long‐latency interhemispheric inhibition may suggest that two phases of interhemispheric inhibition are implemented in distinct circuits with different functional meaning.